Analisis Penerapan Syariah Compliance terhadap Kepuasan Nasabah - Nikmah Dalimunthe; Aldi Bastian (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
Abstract This study analyzes the perceptions of 100 customers of Bank Sumut Syariah KCP Karya regarding the implementation of Shariah Compliance by the bank. The research findings indicate that the majority of customers affirm the alignment of products with Shariah principles and express trust in the written Shariah contracts. However, concerns arise regarding the reliability of financial reports and the handling of customer service issues by the bank. Education regarding Shariah principles and the bank's transparency is considered crucial to enhance customer understanding. While most customers are satisfied with the adherence to Shariah principles, there exist differing views concerning the bank's reliability in addressing customer service matters. This underscores the need for improved service and simplified banking procedures to meet customer expectations. While the majority of respondents are content with the appearance and service provided by bank employees, some recommend enhancing comprehension of Shariah products and better socialization regarding the applied Shariah principles. In conclusion, this study emphasizes the significance of education in Shariah principles, transparency, and improved service to maintain and enhance customer satisfaction and trust in Bank Sumut Syariah KCP Karya. Keyword : Syariah Compliance, Shariah Principles, Customer Satisfaction.